Characterizing and Engineering Thioesterases as Biocatalysts for Macrocyclization - Brazeau-Henrie, Jordan (Université d'Ottawa / University of Ottawa, 2024)
Natural products (NP) present themselves as complex molecules with useful and potent biological activities. Notably, macrocyclic NP have garnered significant attention for defying the prototypical "rule of 5" yet retaining optimal pharmacological properties, and the ability to bind to targets with high affinity and specificity. While synthetic macrocyclization poses considerable challenges, nature effortlessly generates these complex molecules using thioesterase (TE) domains positioned at the C-terminus of modular biosynthetic machinery. This has spurred researchers to explore the use of TEs as in vitro macrocyclization biocatalysts, enabling the chemoenzymatic synthesis of numerous macrocycles. In the context of the existing literature on TEs, we proposed two models to provide a rational framework for understanding TE-mediated macrocyclization. The research presented here describes the characterization of two non-ribosomal peptide synthetase (NRPS) TE domains and their use as biocatalysts for the chemoenzymatic synthesis of two cyclic depsipeptide NP. Unlike other characterized NRPS TEs, these two demonstrated the ability to catalyze macrolactonization with minimal competing hydrolysis reactivity, making them promising biocatalysts. An uncommon tandem TE domain was also characterized, revealing its tolerance for N-terminal peptide modification, peptide sequence composition and stereochemical configuration of the nucleophile used for ring closure. These attributes make it a compelling candidate for the development of a general peptide macrocyclization biocatalyst. Finally, the first extensive engineering of a polyketide synthase (PKS) TE was undertaken via a rational protein design approach and an LCMS-based screening method. Four variants were identified with improved macrocyclization activity over wild-type (WT), highlighting the utility and success of TE protein engineering. This pioneering engineering project serves as a foundation for future TE engineering projects that will generate useful enzymes with optimized activities. Overall, the research presented further develops the field of macrocyclization biocatalysis by showcasing the utility and engineering of TE domains.
Keywords: Thioesterases; Biocatalysis; Macrocyclization; Protein engineering; Chemoenzymatic synthesis